Contact lens prescribing in Canada 2011 - Jones, Deborah; Woods, Craig; Efron, Nathan; Morgan, Philip (Canadian Journal of Optometry, 2012)
The annual survey to collect data on the contact lens prescribing preferences of practitioners has continued for 12 years in Canada. Practitioners were surveyed for information on the first 10 patients they fitted with contact lenses immediately after receipt of said survey. A total of 121 completed surveys were returned, detailing contact lens fittings for 1,184 patients. Of the patients fitted with contact lenses, the results indicated that the majority were prescribed soft lenses. The preferred modality was monthly planned replacement and over 67 per cent of the soft lens fits were made of silicone hydrogel materials. Of the rigid lens fits, the majority were prescribed for daily wear, as the overnight use of rigid lenses appears to be mainly for orthokeratology. Practitioners are recommending multipurpose solutions for the majority of their soft lens patients (85.6%).